Peranan Komunikasi Guru dalam Implementasi Kurikulum 2013 - Vusparatih, Dina Sekar (Humaniora, 2014)
Curriculum 2013 has been officially implemented in all schools in Indonesia. This curriculum has quite a fundamental change in the competencies to be achieved. These changes lead to changes in the profile of students and teachers are expected. These changes lead to conversion in the expected profile of students and teachers. Teacher, a leading role in the successful implementation of the curriculum in schools, is required to create an interactive learning environment in which students and teachers participate actively. The additional hours of study is intended to provide sufficient time for the two-way communication. However, most of the teachers are not ready to create an active space of two-way communication. In fact, the communication competency is the first competency to be achieved in the curriculum in 2013 and became an important teaching method during the learning process. Therefore, the communication ability of the teachers is very important in the success of the implementation of Curriculum 2013. Teachers must be able to communicate effectively in accordance with their role as a leader and facilitator in the classroom. Giving explanations, asking questions and listening are three effective communication techniques that should be owned by the teacher during this 2013 curriculum. If all three techniques have been mastered and can be implemented correctly then the target of Curriculum 2013 can be achieved.